Discussion on the necessity and urgency for developing science and technology and integrating science and technology into socio-economic development - Hoang Xuan Long; Hoang Lan Chi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
The article highlights the complex nature and intrinsic relevance of the necessity and urgency for developing S&T and integrating it into socio-economic development which differs from the prevalent simplistic perception of these issues. There are many fundamental components to the necessity and urgency of developing S&T and integrating it into socio-economic development, and each of these fundamental elements has several levels. The new approach not only clarifies the content, scope, and nature of the necessity and urgency of S&T development and links S&T with socio-economic, but also allows to explain the difference in success in practice and shows ways to proactively enhance effectiveness and promote the significance of the necessity and urgency of developing S&T and integrating it into socio-economic development in Vietnam. Code: 22121202